2023
DOI: 10.3390/cells12050694
|View full text |Cite
|
Sign up to set email alerts
|

Intrahippocampal Inoculation of Aβ1–42 Peptide in Rat as a Model of Alzheimer’s Disease Identified MicroRNA-146a-5p as Blood Marker with Anti-Inflammatory Function in Astrocyte Cells

Abstract: Circulating microRNAs (miRNAs) have aroused a lot of interest as reliable blood diagnostic biomarkers of Alzheimer’s disease (AD). Here, we investigated the panel of expressed blood miRNAs in response to aggregated Aβ1–42 peptides infused in the hippocampus of adult rats to mimic events of the early onset of non-familial AD disorder. Aβ1–42 peptides in the hippocampus led to cognitive impairments associated with an astrogliosis and downregulation of circulating miRNA-146a-5p, -29a-3p, -29c-3p, -125b-5p, and-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Potential confounding variables were minimised by placing the cages at the same level, the order of the evaluations was always the same and they were always performed at the same time, between 09:00 and 13:00. Animal handling and experimental procedures were approved by the ethical guidelines of the Universidad Peruana Cayetano Heredia System (CIEA-102069) [ 8 ]. Rats were obtained from the bioterium of the Research and Development Laboratory, Universidad Peruana Cayetano Heredia, Lima, Peru.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Potential confounding variables were minimised by placing the cages at the same level, the order of the evaluations was always the same and they were always performed at the same time, between 09:00 and 13:00. Animal handling and experimental procedures were approved by the ethical guidelines of the Universidad Peruana Cayetano Heredia System (CIEA-102069) [ 8 ]. Rats were obtained from the bioterium of the Research and Development Laboratory, Universidad Peruana Cayetano Heredia, Lima, Peru.…”
Section: Methodsmentioning
confidence: 99%
“…They were kept under temperature (25 ± 2 °C) and humidity (60%) controlled conditions. The rats' behaviour was monitored daily by animal care staff to ensure that the animals were safe and healthy [ 8 ]. Factors considered in deciding whether to euthanise before the planned end of the experiment included weight loss; severe pain that could not be controlled; tumour growth; coughing, wheezing or severe nasal discharge; nervous signs such as tremors, convulsions and paresis; incapacitation and other behavioural signs of distress, but not adverse events were observed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, NF- κ B was infused into the hippocampus of rats and it was found that the NF- κ B pathway was activated; miRNA-146a-5p was upregulated, leading to a downregulation of IRAK-1 expression and a doubling of astrocytes. After treatment with the NF- κ B inhibitor BMS-345541, the expression of miRNA-146a-5p in astrocytes was significantly reversed, and IRAK-1 could be rescued, indicating that miRNA-146a-5p may pass NF- κ B pathway negative feedback loop which exerts anti-inflammatory function [ 122 , 123 ]. Other studies have confirmed that miR-15b may directly target BACE1 and downregulate its expression by inhibiting NF- κ B activation, reducing the production and accumulation of A β , and reducing the secretion of inflammatory cytokines [ 124 ].…”
Section: Effect Of Mirnas On Neurodegenerative Diseasesmentioning
confidence: 99%
“…On the other hand, the use of animal models has been reported to evaluate cognitive problems associated with different pathologies, such as Alzheimer’s disease, which have been widely studied using behavioral tests ( Aquino et al, 2023 ), and to a lesser extent neuroinfectious diseases caused by viruses ( Dittrich et al, 1989 ; Elmore et al, 2014 ), parasites ( Parvin et al, 2016 ) and bacteria ( Becerril-Villanueva et al, 2018 ), where they have also reported cognitive deterioration in addition to alterations in hippocampus, decreased learning, and short- and long-term memory loss ( Tolman and Gleitman, 1949 ; Arime and Akiyama, 2017 ). In the case of memory studies in NCC, these are scarce.…”
Section: Introductionmentioning
confidence: 99%